Pengorganisasian Kelas dalam Pembelajaran Daring Masa Pandemi di MI - Susanti, Yuanita; Guntur, Muhammad; Jaya, Rahmat; Rais, Rinovian; Alfiyanto, Afif; Hidayati, Fitri (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2022)
The purpose of this study was to find out how to organize classes during online learning during the covid-19 pandemic, and to find out what the inhibiting and supporting factors were at MI Assegaf Palembang. This study uses qualitative research methods, using a descriptive approach. Data collection techniques in this study through observation, interviews, and documentation. Informants in this study were principals as key informants, education staff, and teachers as supporting informants. The data analysis used in this research is data reduction, data presentation, and conclusion drawing. The result of this study is that classroom organization during online learning during the pandemic has been going well, according to indicators that support the course of classroom organization, namely, curriculum, teachers, students, facilities, and media. The results of these indicators are 1) curriculum, which is very supportive of the course of the class organization; 2) teachers, that is, almost all of the teacher's tasks at the time of class organization have gone well; 3) students, namely in terms of class organization, students have carried out their duties appropriately; 4) facilities, namely in online learning, the facilities used are by the process; 5) media, namely the online learning process using WhatsApp media more often. The supporting factors are facilities owned by students such as cellphones, laptops, and internet access. The inhibiting factor is that some students still don't have cellphones and some parents still don't understand using cellphones for online learning.